Fentanyl activates opposing opioid and non-opioid receptor systems that control breathing - Baby, Santhosh M.; May, Walter J.; Getsy, Paulina M.; Coffee, Gregory A.; Nakashe, Tej; Bates, James N.; Levine, Alan; Lewis, Stephen J. (Frontiers in Pharmacology, 2024)
Fentanyl elicits profound disturbances in ventilatory control processes in humans and experimental animals. The traditional viewpoint with respect to fentanyl-induced respiratory depression is that once the effects on frequency of breathing (Freq) and tidal volume (TV) and minute ventilation (MV = Freq x TV) are resolved then depression of breathing is no longer a concern. The results of the present study challenge this concept with findings that whereas the apparent inhibitory effects of fentanyl (75 g/kg, IV) on Freq, TV and MV in adult male rats was fully resolved within 15 min, many other fentanyl-induced responses were in full effect, including opposing effects on respiratory timing parameters. For example, although the effects on Freq were resolved at 15 min, inspiratory duration (Ti) and end inspiratory pause (EIP) were elevated whereas expiratory duration (Te) and end expiratory pause (EEP) were diminished. Since the effects of fentanyl on TV had subsided fully at 15 min, it would be expected that administration of an opioid-receptor antagonist would have minimal effects if the effects of fentanyl on this and other parameters had resolved. We now report that intravenous injection of a 1.0 mg/kg dose of the peripherally-restricted OR antagonist, methyl naloxone (naloxone methiodide, NLXmi), did not elicit arousal but did elicit some relatively minor changes in Freq, TV, MV, Te and EEP but pronounced changes in Ti and EIP. In contrast, the injection of a 2.5 mg/kg dose of NLXmi, elicited pronounced arousal and dramatic changes in many variables including Freq, TV and MV, that were not associated with increases in non-apneic breathing events such as apneas. The two compelling conclusions from this study are (1) blockade of central ORs produced by the 2.5 mg/kg dose of NLXmi elicits pronounced increases in Freq, TV and MV in rats in which the effects of fentanyl had apparently resolved, and (2) it is apparent that fentanyl had induced the activation of two systems with counter-balancing effects on Freq and TV, one an opioid receptor inhibitory system and the other a non-OR excitatory system.